Pasang Ri Kajang in Developing Youth Character of Environmental Love in Tana Toa Kajang - Tajibu, Kamaluddin (Jurnal Adabiyah, 2020)
The study is aimed to determine the values of Pasang ri Kajang in building the youth character of environmental love in Tana Toa Village, Kajang District, Bulukumba Regency. This type of research is a qualitative descriptive study with intercultural communication as the approach of study. The data are obtained from Ammatoa with its traditional stakeholders, the Ammatoa youth community as well as community leaders who have concerned with Ammatoa community members. Data are analyzed using semiotics analysis. The results of the Pasang believed to be the will of Turiek Akrakna, which is handed down to Ammatoa I, and passed onto his successor, Ammatoa, is a source of values that govern the world life in its journey towards a life in the days to come. The noble values that can be implemented into conservation character education from the local wisdom of the Ammatoa indigenous people are about 1) Love to Almighty God and His universe; 2) Be responsibility, discipline, and independence; 3) Be honest, 4) Be scrupulous; 5) Work hard in preserving nature; 6) Do justice; 7) Be Modesty; and 8) Love for peace and unity. These values are very suitable to be implemented in building the character of children to love the environment, especially the forest environment.كان الغرض من هذه الدراسة هو تحديد قيم Pasang ri Kajang في بناء شخصية الشباب في الحب البيئي في قريةTana Toa ، منطقةKajang ، محافظة Bulukumba  هذا النوع من البحث هو دراسة وصفية نوعية مع نهج تواصل بين الثقافات. تم الحصول على مصادر البيانات منAmmatoa  مع أصحاب المصلحة التقليديين وأفراد المجتمع (الشباب) ، وكذلك قادة المجتمع الذين لديهم قلق لأفراد مجتمع Keammatoaan .تم تحليل البيانات باستخدام تحليل السيميائية. كانت نتائج الأزواج، التي يعتقد أنها إرادةTuriek Akrakna ، والتي تم تسليمها إلىAmmatoa I ، وتم نقلها إلىAmmatoa ، خليفته، مصدرًا للقيم التي حكمت حياة العالم في رحلته إلى الحياة في الأيام القادمة. القيم النبيلة التي يمكن تنفيذها في الحفاظ على تعليم الشخصية من الحكمة المحلية لسكان أماتوا الأصليين هي 1) حب الله والكون ومحتوياته، 2) المسؤولية والانضباط والاستقلالية، 3) صادق، 4) شامل، 5 ) العمل الشاق في الحفاظ على الطبيعة، 6) العدل، 7) البساطة، 8) حب السلام والوحدة. هذه القيم مناسبة جدًا ليتم تنفيذها في بناء شخصية الأطفال الذين يحبون البيئة، وخاصة بيئة الغابات. Tujuan penelitian ini untuk mengetahui nilai-nilai Pasang ri Kajang dalam membangun karakter pemuda cinta lingkungan di Desa Tana Toa Kecamatan Kajang Kabupaten Bulukumba. Jenis penelitian ini adalah penelitian deskriptif kualitatif dengan pendekatan komunikasi antarbudaya. Sumber data diperoleh dari Ammatoa dengan para pemangku adatnya, Warga masyarakat (pemuda), serta tokoh masyarakat yang mempunyai kepedulian terhadap warga masyarakat Keammatoaan. Data dianalisis dengan menggunakan analisis semiotika. Hasil penelitian Pasang yang diyakini sebagai kehendak dari Turiek Akrakna yang diturunkan kepada Ammatoa I, dan diteruskan kepada Ammatoa penerusnya, merupakan sumber nilai-nilai yang mengatur kehidupan dunia dalam perjalanannya menuju kehidupan di hari kemudian. Nilai-nilai luhur yang dapat diimplementasikan ke dalam pendidikan karakter konservasi dari kearifan lokal masyarakat adat Ammatoa adalah: 1) cinta kepada Tuhan dan alam semesta beserta isinya, 2) tanggung jawab, disiplin, dan mandiri, 3) jujur, 4) teliti, 5) kerja keras dalam pelestarian alam, 6) keadilan, 7) Kesederhanan , 8) cinta damai dan persatuan. Nilai-nilai tersebut sangat cocok diimplementasikan dalam membangun karakter anak akan cinta lingkungan terutama lingkungan hutan.